Combining problem-solution categories and communicative acts: an analysis of Malaysian and British business journalistic texts - Mohamad Ali, Afida (IDOSI Publications, 2013)
Textual features are evidence of a community’s routines for producing knowledge. In Language for Special Purposes (LSP), it is generally accepted that through text, it is possible to explore the activity of knowledge-making in a professional community, particularly in specialized written discourse. This activity or communicative tasks are realized as communicative acts which contains the writer’s / speaker’s thoughts and intentions. The assumption of the present research is that the communicative tasks that a specialist performs in the real world can be manifested in the specialized text and that business journalistic discourse contains problems and solutions. By comparing Malaysian (MB) and British (MT) business journalistic texts, this paper examines the feasibility of combining [13] and [5] theories to search for speech acts that fall into the Problem- Solution categories. Using a corpus linguistics methodology, the results indicate that 1) there are significant differences in the frequencies of communicative acts underlying the Problem and Solution in MB compared with MT and 2) there are no one-to-one mappings of communicative functions onto either a Problem or a Solution.